2001
DOI: 10.1897/1551-5028(2001)020<1792:aisdot>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities in Sexual Development of the Amphipod Gammarus Pulex (L.) Found Below Sewage Treatment Works

Abstract: Increasing numbers of widely used industrial, agricultural, and natural chemicals are known to elicit endocrine-disrupting effects in a wide range of vertebrate and invertebrate species. The objective of this study was to determine whether the sexual development of the freshwater crustacean Gammarus pulex (L.) was affected below sewage treatment works (STW) previously known to contain endocrine-disrupting chemicals in their effluent. The gonadal structure, external sexual characteristics, and size of gammarids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
4

Year Published

2005
2005
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 23 publications
0
26
0
4
Order By: Relevance
“…Sundelin and Eriksson [70] reported high frequencies of malformed embryos in the deposit-feeding amphipod M. affinis, in which high concentrations of polycyclic aromatic hydrocarbons were measured in settling particulate matter and bottom sediments. An abnormal structure of oocytes in vitellogenesis was reported for the amphipod G. pulex sampled at river sites where the natural steroids 17b-estradiol and estrone had been detected, together with male fish producing vitellogenin, a typical biomarker of exposure to estrogenic substances [116]. However, the cause of the pathologies in G. pulex is uncertain because, in the laboratory, crustaceans (crabs and shrimps) did not produce vitellin in response to estrogens [117].…”
Section: Effects Of Endocrine-disrupting Contaminants On Amphipodsmentioning
confidence: 99%
“…Sundelin and Eriksson [70] reported high frequencies of malformed embryos in the deposit-feeding amphipod M. affinis, in which high concentrations of polycyclic aromatic hydrocarbons were measured in settling particulate matter and bottom sediments. An abnormal structure of oocytes in vitellogenesis was reported for the amphipod G. pulex sampled at river sites where the natural steroids 17b-estradiol and estrone had been detected, together with male fish producing vitellogenin, a typical biomarker of exposure to estrogenic substances [116]. However, the cause of the pathologies in G. pulex is uncertain because, in the laboratory, crustaceans (crabs and shrimps) did not produce vitellin in response to estrogens [117].…”
Section: Effects Of Endocrine-disrupting Contaminants On Amphipodsmentioning
confidence: 99%
“…Gross et al (2001) reported that high numbers of females displayed abnormal vitellogenic oocytes and a reduced male/female size differential in amphipods (Gammarus pulex) found below sewage treatment works known to contain endocrine-disrupting chemicals in their effluent.…”
Section: Resale or Republication Not Permitted Without Written Consenmentioning
confidence: 99%
“…Other examples of effects in invertebrates include abnormal levels of intersexuality in several species of marine harpacticoid copepods along sewage-contaminated coasts of Scot-land (Moore & Stevenson 1991, 1994, the occurrence of intersex in a population of lobsters exposed to sewage effluent (Sangalang & Jones 1997), masculinisation of freshwater copepod species in North American lakes (Sillett & Stemberger 1998) and the presence of dual-gender imposex in freshwater crabs inhabiting Japanese TBT-uncontaminated mountain streams (Takahashi et al 2000). Gross et al (2001) reported that high numbers of females displayed abnormal vitellogenic oocytes and a reduced male/female size differential in amphipods (Gammarus pulex) found below sewage treatment works known to contain endocrine-disrupting chemicals in their effluent.…”
Section: Introductionmentioning
confidence: 99%
“…Morphological and histological changes resulting from exposure to EDs have been documented in fish, amphibians, reptiles, mammals, and arthropods (e.g., Gross et al, 2001;Vandenbergh et al, 2003;Schirling et al, 2006). In mysids, morphology and histology have not been considered widely as a measurable endpoint in toxicological studies.…”
Section: Morphology and Histologymentioning
confidence: 99%